Telomeres and stress: Promising avenues for research in psycho-oncology - Eleanor Law; Afaf Girgis; Lambert Sylvie; Janelle Levesque; Hilda Pickett (Elsevier, 2016)
A cancer diagnosis and subsequent treatment is a stressful experience with the potential for long-term health consequences for both patients and their caregivers. It is now well-established that psychological stress is associated with detrimental effects on physical health. Recent studies have investigated the link between telomeres, the protective cap at the end of chromosomes, and stress, suggesting that stress potentially impacts on cellular aging through telomere shortening, with subsequent consequences for health. This review aims to familiarize the reader with the pertinent literature exploring the relationship between telomeres and psychological and behavioral factors and propose future directions for telomere research in psycho-oncology.